Perbandingan Kadar Coffein pada Ekstrak Daun dan Bunga Kopi di Tirtoyudo Kabupaten Malang dengan Pengeringan Suhu 60°C, 80°C dan 100°C - Rennata, Adella Vrida; Sugianto; Hasana, Ani Riani (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The coffee plant (Coffea sp) has been known to the public for a long time, coffee can be known as a plant for beverages that is most used by people from all levels. Caffeine is a type of alkaloid that is often found in coffee beans. Objective: To determine the highest levels of caffeine in coffee leaves and flowers. Method: The method used was experimental with a True Experimental Research design, Post-Test Only Control Group design. Samples of coffee leaves and flowers were subjected to drying at 60°C, 80°C and 100°C, then extracted using distilled water as a solvent. The standard caffeine solution was made in a series of solutions with concentrations of 1, 2, 3, 4, and 5 ppm, then the absorbance was measured using UV - Vis spectrophotometry to form a calibration curve. The absorbance of the extract was measured at a wavelength of 273 nm using UV-Vis spectrophotometry, then the caffeine concentration was calculated using a calibration curve. Next, caffeine levels were determined and statistical data analysis was carried out. Results: Coffee leaf caffeine content with drying at 60°C (0.0012 mg), followed by drying at 80°C (0.0004 mg) and drying at 100°C (0.0010 mg). For coffee flower samples, drying at a temperature of 60°C (0.0027 mg), followed by drying at a temperature of 80°C (0.0203 mg) and drying at a temperature of 100°C (0.0210 mg). The results of caffeine levels were analyzed statistically using the ANOVA test, there were no significant differences. Conclusion: The highest caffeine content in leaf samples was found at a drying temperature of 60°C (0.0012 mg), while in flower samples it was found at a drying temperature of 100°C (0.0210 mg).